Students’ Perception on The Use of Wordwall.Net as The Media for Learning English Grammar - Iin Nirwana; Rizky Takriyanti; Uyun Nafiah; Widia Salsabila (Journal in Teaching and Education Area, 2025)
The research aimed to know students' perception on the use of Wordwall.net as the media for learning English grammar at Junior High School Darul Arifin Muaro Jambi. This research used descriptive quantitative method with a survey design. This method is considered as the right approach for this type of research. The sample of this research is all students of ninth grade from class 9I,9J,9K,9L, and 9M at Junior High School Darul Arifin Muaro Jambi which 102 students. The instrument used in data collection was questionnaires. The data was collected using a close-ended questionnaire based on a Likert scale and analyzed with SPSS Version 26. The findings indicated that the use of Wordwall.net was clearly positive for the students on the indicators of feeling (86,04%), attitude (80,3%), and engagement (82,62%). The final results of the research showed the students' perceptions on the use of Wordwall.net as the media for learning English grammar are in very good category with percentage 83%.